Impacts of COVID-19 Pandemic on Three IVF Clinics of Jakarta, Indonesia: A Retrospective Qualitative and Quantitative Study - Fira Azzahra; Mulyoto Pangestu; Silvia W Lestari; Gita Pratama (International Journal of Fertility and Sterility, 2023)
Background: Corona virus disease-19 (COVID-19) pandemic also led to a reduction or even the suspension of electivehealth services. These decisions affected in vitro fertilization (IVF) programs worldwide. Therefore, it is essential to mapthe readiness of IVF clinics in providing safety in this situation and in the future.Materials and Methods: This is a retrospective qualitative and quantitative research done in 2021 that involved three IVFclinics of Jakarta, Indonesia. Those three clinics were government-owned, private-owned, and educational and trainingcenter. The qualitative data of each clinic’s readiness towards COVID-19 was obtained from interviews with the clinicsstaff. The quantitative data were collected from the clinics patients’ number and demographic data from 2019-2021 as wellas from COVID-19 databases. Both data sets were analysed descriptively and only for the quantitative analysis Stata version16 was used.Results: There were changes in the domiciles and number of patients attending the three clinics. The ratio of patientsfrom Jakarta increased while patients from outside Java Island decreased. There was a drop in annual patient numbersin 2020. However, from June 2020 to December 2021, the number of monthly IVF cycles increased significantly by 3.5cycles per month (P=0.001). There was no association between IVF patients’ attendance numbers and COVID-19 cases(P=0.785). One of the clinics had a negative pressure operating theatre, which made them more confident in treatingpatients with COVID-19 positive and made them even had higher IVF cycles started than the pre-pandemic period.Conclusion: Those three clinics are prepared in facing COVID-19, as they complied with government regulations. Asthe COVID-19 pandemic progressed, the number of patients gradually returned to normal.